1983
DOI: 10.1093/infdis/148.2.322
|View full text |Cite
|
Sign up to set email alerts
|

Perforated and Gangrenous Appendicitis: An Analysis of Antibiotic Failures

Abstract: The relationships between resistant pathogens, serum levels of gentamicin, and the outcomes of gangrenous or perforated appendicitis were analyzed in 147 patients. Failure to cure the infection occurred significantly more frequently among patients treated with cefoperazone or cefamandole than among those treated with clindamycin and gentamicin in combination. The failures were associated with recovery of resistant Bacteroides fragilis from intraoperative cultures. Pseudomonas species were also associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…might have had a particular benefit from the aminoglycosidecontaining regimen. Such a benefit was suggested by one study (18).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…might have had a particular benefit from the aminoglycosidecontaining regimen. Such a benefit was suggested by one study (18).…”
Section: Discussionmentioning
confidence: 89%
“…Lau et al (22) also showed a failure rate with cefoperazone (20%) significantly higher than that with moxalactam (8%) in patients with perforated or gangrenous appendicitis. In a further analysis of data from the first study, the likelihood of failure was found to be greatest in patients from whom B. fragilis isolated from the abdominal cavity at surgery was resistant to the antibiotics used (18). A previous report likewise suggested that failures of treatment of intra-abdominal infection with moxalactam were predicted by the finding of moxalactam-resistant anaerobic bacteria in the initial cultures (30).…”
Section: Comparison Of Trials With and Without An Aminoglycosidementioning
confidence: 91%
See 1 more Smart Citation
“…There are a number of factors which are thought to be predictive of the clinical outcome of intraabdominal sepsis, including the site and extent of infection, the severity of the underlying illness, the nutritional status of the patient, the operative procedure, and the antimicrobial therapy used (1,6,9,12).…”
Section: Discussionmentioning
confidence: 99%
“…The issue of clinical correlation with anaerobic susceptibility testing has been raised recently (8) (9). However, the question of "relative" susceptibility with an "active" agent like cefoxitin and the role of susceptibility to outcome has never been addressed.…”
Section: Discussionmentioning
confidence: 99%